KUALITAS PETIS HASIL INDUSTRI RUMAH TANGGA DI DESA SOCAH KECAMATAN SOCAH BANGKALAN MADURA TAHUN 2016 - Dema Indah Sulistyorini; Sukiran Al Jauhari; Siti Surasri (Poltekkes Kemenkes Surabaya, 2017)
ABSTRACTPetis is a pasta-like food made of fresh fish/shrimp. Petis is usually produced by IRT innon sanitary way. These conditions allow the pollution/contamination of the petis production, eitherby microorganisms, physical objects, or chemicals. This study aims to determine the quality ofpetis production in Socah, Bangkalan, Madura.This research is a descriptive research. Data were collectetd by observations andlaboratory tests. There were 3 petis industries in Socah, where we took samples.The results showed that the quality of petis in physical aspects were not qualified, thechemical aspects were good, and microbiological aspects of two samples were not eligible. Sanitaryconditions of the production-sites were less than 53.4%, but the domestic industry‟s score were68%.The final conclusion is that petis production in Socah Madura is ineligible, on physical andmicrobiological aspect. Only in chemical aspect they were eligible. It is recomended to the peopleto be careful in buying any petis from Socah, test the smell and texture before used for dressing infood.Keywords : Petis, Physical, Chemical and Microbiological Quality.